Pengembangan E-Modul dengan Pendekatan Problem Based Learning untuk Peserta Didik SMA/MA Kelas XI Materi Gejala Gelombang - Faqih Dinal Malik Sidik; Ika Kartika (Jurnal Penelitian Pembelajaran Fisika, 2020)
This research aims to: (1) development of e-module with problem based learning approach, (2) obtaining the quality of e-module with problem based learning approach based on material expert, media expert and physics teacher assessment, (3) Obtaining the response from student and enforceability of e-module with problem based learning approach. This research belongs to Research and Development (R&D). Development is done by referring to the procedural model. This development research procedure is based on 4-D model which includes 4 steps, namely (1) Define, (2) Design, (3) Develop, (4) Disseminate. This research is done until Development steps. The research instrument are criticism and validator suggestion sheet, e-module quality assessment sheet, student response sheet and enforceability observastion sheet. The result of this research is e-module with problem based learning approach. The e-module quality based on assessment of material expert, media expert and physics teacher has average score 3,62; 3,80; and 3,92 with a very good category. Student’s responses on small field test have average score 0,88 with agree category. Result from the enforceability of e-module on 3th and 4th problem based learning steps in e-module has not been implemented. Other steps as a whole have been well implemented on the large field test.